Major surgery in an osteosarcoma patient refusing blood transfusion: case report - Dhanoa, A.; Singh, V.A.; Shanmugam, R.; Rajendram, R. (2010)
We describe an unusual case of osteosarcoma in a Jehovah's Witness patient who underwent chemotherapy and major surgery without the need for blood transfusion. This 16-year-old girl presented with osteosarcoma of the right proximal tibia requiring proximal tibia resection, followed by endoprosthesis replacement. She was successfully treated with neoadjuvant chemotherapy and surgery with the support of haematinics, granulocyte colony-stimulating factor, recombinant erythropoietin and intraoperative normovolaemic haemodilution. This case illustrates the importance of maintaining effective, open communication and exploring acceptable therapeutic alternative in the management of these patients, whilst still respecting their beliefs.